Preparation, microstructure and hydrogen sorption properties of nanoporous carbon aerogels under ambient drying - Tian, Hu-Yong; Buckley, Craig; Mule, S.; Paskevicius, Mark; Dhal, Bipin (IOP, 2008)
Organic aerogels are prepared by the sol–gel method from polymerization of resorcinol with furfural. These aerogels are further carbonized in nitrogen in order to obtain their corresponding carbon aerogels (CA); a sample which was carbonized at 900 °C was also activated in a carbon dioxide atmosphere at 900 °C. The chemical reaction mechanism and optimum synthesis conditions are investigated by means of Fourier transform infrared spectroscopy and thermoanalyses (thermogravimetric/differential thermal analyses) with a focus on the sol–gel process. The carbon aerogels were investigated with respect to their microstructures, using small angle x-ray scattering (SAXS), transmission electron microscopy (TEM) and nitrogen adsorption measurements at 77 K. SAXS studies showed that micropores with a radius of gyration of <0.35 ± 0.07 to 0.55 ± 0.05 nm were present, and TEM measurements and nitrogen adsorption showed that larger mesopores were also present. Hydrogen storage properties of the CA were also investigated. An activated sample with a Brunauer–Emmett–Teller surface area of 1539 ± 20 m2 g−1 displayed a reasonably high hydrogen uptake at 77 K with a maximum hydrogen sorption of 3.6 wt% at 2.5 MPa. These results suggest that CA are promising candidate hydrogen storage materials.